219 Documentation of Scrotal Examination in Male Children with Abdominal Pain. (4th May 2021) - Da Costa, K; Watson, S; Perks, H; Battersby, C
Abstract: Background: Abdominal pain is a common presentation in all age groups with 7-10% of emergency department admissions. Method: This registered audit looks at male children (aged <16), admitted with abdominal pain during this period. Approximately 2, 877 children under the age of sixteen were admitted, 1, 582 males. This equates to 55% of children admitted within 3 months. Manual note analysis from ED records identified 53 males <16 years of age with abdominal pain for inspection of documentation. Results: 45% of inspected notes had documented genital and scrotal examination, none of which had a documented consent. In addition, 21% had a documented chaperone for the intimate examination. None of the cases had BOTH consent and presence of chaperone documented. Conclusions: A common presentation in children lacks significant elements of documentation. This is noted in multiple specialties. Potentially overlooked aspects of examination can lead to missed or delayed identification of time sensitive diagnosis namely testicular torsion, with possible substantial legal, professional, and financial consequences. To improve the quality of documentation, education at junior doctor level has been carried out, with further analysis to take place and with the view to incorporate the three elements of an intimate examination: consent, chaperone, and findings.